RFID BASED LIBRARY AUTOMATION SYSTEM USING AT89S52 (International Journal of Food and Nutritional Sciences, 2022)
Radio Frequency Identification (RFID) Card Readers provide a low-cost solution to read passive RFID transpondertags up to 2 inches away. The RFID Card Readers can be used in a wide variety of hobbyist and commercialapplications, including access control, automatic identification, robotics navigation, inventory tracking, paymentsystems, and car immobilization